2020
DOI: 10.1177/1076029620950837
|View full text |Cite
|
Sign up to set email alerts
|

Association of Acidemia With Short-Term Mortality of Acute Myocardial Infarction: A Retrospective Study Base on MIMIC-III Database

Abstract: Acute myocardial infarction (AMI) is a leading cause of death and not a few of these patients are combined with acidemia. This study aimed to detect the association of acidemia with short-term mortality of AMI patients. A total of 972 AMI patients were selected from the Medical Information Mart for Intensive Care (MIMIC) III database for analysis. Propensity-score matching (PSM) was used to reduce the imbalance. Kaplan-Meier survival analysis was used to compare the mortality, and Cox-proportional hazards mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…In order to better study the treatment and prognosis of CCU patients, we chose to use the MIMIC database, which is difficult but with a large amount of data on critically ill patients, as the data source for the study, which ensures the reliability of the entire study results. All the C-indexes shown in the results are close to 1, which shows that the model constructed in this study has good judgment ability and is better than the model reported in the related literature [30][31][32]. The result of the calibration curve shows that this study still has a high consistency.…”
Section: Discussionsupporting
confidence: 58%
“…In order to better study the treatment and prognosis of CCU patients, we chose to use the MIMIC database, which is difficult but with a large amount of data on critically ill patients, as the data source for the study, which ensures the reliability of the entire study results. All the C-indexes shown in the results are close to 1, which shows that the model constructed in this study has good judgment ability and is better than the model reported in the related literature [30][31][32]. The result of the calibration curve shows that this study still has a high consistency.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have shown that BE is one of the most important tools for determining the severity of illness in acute care settings ( 9 , 10 , 13 , 14 ). Miñana et al revealed that admission pH, arterial PaO 2 , and PaCO 2 had no association with all-cause mortality in patients with HF ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xu et al found that the higher anion gap (AG) was significantly associated with an increased risk of mortality, and the measure of AG can be a robust and reliable predictor of AMI mortality during follow-up ( 7 ). In a recent study, Zhang et al concluded that acidemia may increase the 30-day survival rate and 90-day survival rate of patients with AMI admitted to the ICU, while acidemia is typically diagnosed based on the ABG with pH < 7.35 ( 9 ). However, Miñana et al found that arterial PaO 2 , PaCO 2 , and pH did not correlate with all-cause long-term mortality in patients diagnosed with AHF ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…13 Another research presented that 1 of the coagulation indicators, PT, is regarded as an independent predictor for 2-year mortality in acute myocardial infarction patients. 14 McClintock compared biomarkers of coagulation and fibrinolysis between survivors and non-survivors, indicating that coagulation and fibrinolysis predict mortality in patients with lung-protective ventilation. Moreover, the levels of thrombomodulin and plasminogen activator inhibitor 1 (PAI) are significantly higher in non-survivors.…”
Section: Discussionmentioning
confidence: 99%